Presbyopia developed earlier during the COVID-19 pandemic - Kazuno Negishi (Public Library of Science (PLoS), 2021)
Purpose The aim of this cohort study was to evaluate the development and progression of presbyopia and the status of dry eye-related symptoms from 2017 to 2020, to assess the impact of the COVID-19 pandemic. Methods Near add power at 30 cm was measured in 339 participants aged between 40 and 55 from 2017 to 2021 at Japanese eye clinics. Regression analysis of near add power and age was analyzed to compare 2017 with later years up to the pandemic. The prevalence of dry eye-related signs and six common symptoms were compared. Results The number and mean age (y) of participants were 183 (48.6±4.1) in 2017, 46 (51.3±7.5) in 2019, and 110 (49.2±3.7) in 2020–21, respectively. The mean progression rate of near add power (D/y) was 0.13 for 2017, 0.09 for 2019 (P = 0.028, vs 2017), and 0.08 for 2020–21 (P<0.001, vs 2017). The slope (rate of presbyopia progression) became flatter from 2017 to 2021 and the estimated near add power at the age of 40 increased from 2017 to 2020–2021, implicating presbyopia developed earlier and worsened during the study period. The 2017 values were comparable with previous studies described in 1922 and 2019. The standardized correlation coefficient between age and near add power was 0.816 for 2017, 0.671 for 2019 (P = 0.084, vs 2017), and 0.572 for 2020–21 (P<0.001, vs 2017). Multiple regression analysis revealed age and COVID-19 pandemic were significantly correlated with near add power. The prevalence of dryness irritation, and pain was greater in 2020–21 than in 2017 with no difference in the prevalence of eye fatigue, blurring, and photophobia. There was no difference in the prevalence of short tear break-up time and positive corneal staining among 2017, 2019 and 2020–21. Conclusion Estimated presbyopia developed earlier and progressed slower from 2017 to 2021, the COVID-19 pandemic. Stress and rapid digitalization related to strict infection control and quarantine might be contributing factors.